If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 2 = -2y + 7 Reorder the terms: 2 + 3y = -2y + 7 Reorder the terms: 2 + 3y = 7 + -2y Solving 2 + 3y = 7 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. 2 + 3y + 2y = 7 + -2y + 2y Combine like terms: 3y + 2y = 5y 2 + 5y = 7 + -2y + 2y Combine like terms: -2y + 2y = 0 2 + 5y = 7 + 0 2 + 5y = 7 Add '-2' to each side of the equation. 2 + -2 + 5y = 7 + -2 Combine like terms: 2 + -2 = 0 0 + 5y = 7 + -2 5y = 7 + -2 Combine like terms: 7 + -2 = 5 5y = 5 Divide each side by '5'. y = 1 Simplifying y = 1
| y=-2.18*5.4+944.68 | | y=-2.18*5.2+944.68 | | 7p+7=2+2p | | y=-2.18*4.5+944.68 | | (x+5)y+2y= | | y=-2.18*5+944.68 | | 4x^2+6x+2=2x+5 | | -64+11y+8=4(4y-3)-4 | | y=-2.18*6+944.68 | | y=-2.18*4+944.68 | | 10c+5c+6d+d= | | 9(x^2+6x+6)=0 | | y=-2.18*2+944.68 | | 7y+3-4y=6 | | n+(n+9)=67 | | -(a+8)=1 | | 3(r+2s)-3r= | | 3x=5x-4(x-3) | | 5x=y+3z | | 32+3x=-8(x+7) | | x=0.85x+0.1275 | | (3n-6)+n=42 | | 25y^2-4=0 | | 6x+7(y+x)= | | x^4+y^4=x^2+y^2 | | -10(h+5)-3=-83 | | (2a^2-a)+(2a-1)= | | 3y^2+10y+3=0 | | d^2-19d+28=0 | | 5+3(3a-8)=-91 | | A+b+a+c= | | -40=8b |